ANALISIS STRATEGI BISNIS DALAM MENINGKATKAN DAYA SAING PADA LAPAK TAMAN GENANG GENIS SUMBAWA BESAR - Maulinda Sarita; S Suprianto (Fakultas Ekonomi dan Manajemen, 2022)
This research aims to determine the business strategy of the Genang Genis Park stalls in increasing competitiveness. This type of research is a descriptive study that aims to describe the internal and external conditions of the Genang Genis Park stalls to determine alternative business strategies in increasing competitiveness. The type of data used is qualitative data in the form of answers from informants obtained directly from the source through interviews. The informants who became the source of the data in this study were the head of Kerato Village, Department of Cooperatives, UMKM, Industry and Trade, Sumbawa District, and 13 stalls owners at Genang Genis Park. Data analysis was performed using the SWOT analysis method. Based on the analysis of data shows the total IFE matrix score is 0.01, while for EFE matrix is 0.20 which place IE of stalls at Genang Genis Park at quadrant I. Position in this quadrant is a favorable situation, because the strengths and opportunities (SO) are greater than weaknesses and threats (WT). The strategy that should be applied to the business at stalls at Genang Genis is supporting aggressive growth (growth strategy oriented) policy, by using the strength possessed to take advantage of opportunities.